2018
DOI: 10.3390/min8070302
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Extinct Seafloor Massive Sulfide Mounds at the TAG, Mid-Atlantic Ridge

Abstract: Over the last decade there has been an increasing interest in deep-sea mineral resources that may contribute to future raw metal supply. However, before seafloor massive sulfides (SMS) can be considered as a resource, alteration and weathering processes that may affect their metal tenor have to be fully understood. This knowledge cannot be obtained by assessing the surface exposures alone. Seafloor drilling is required to gain information about the third dimension. In 2016, three extinct seafloor massive sulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…The TAG active hydrothermal system on the slow-spreading Mid-Atlantic Ridge is exemplary of the footprint of such a potential deposit, with a surface expression on the order of 200 m in diameter, a maximum elevation of ∼50-60 m above the surrounding seafloor (Rona et al, 1986;Humphris and Kleinrock, 1996). Numerous inactive sulfide mounds of similar and even somewhat larger dimensions (e.g., Mir Mound: 400-600 m in diameter) lie within the ∼5 km 2 TAG Hydrothermal Field (Rona et al, 1993;Lehrmann et al, 2018), but are geographically isolated from the active mounds (at least at the surface). Other large sulfide accumulations may be found on intermediate spreading ridges as well as in island arc environments and marginal basins (Hannington and Monecke, 2009;Cherkashov, 2017).…”
Section: Initial Discoveriesmentioning
confidence: 99%
“…The TAG active hydrothermal system on the slow-spreading Mid-Atlantic Ridge is exemplary of the footprint of such a potential deposit, with a surface expression on the order of 200 m in diameter, a maximum elevation of ∼50-60 m above the surrounding seafloor (Rona et al, 1986;Humphris and Kleinrock, 1996). Numerous inactive sulfide mounds of similar and even somewhat larger dimensions (e.g., Mir Mound: 400-600 m in diameter) lie within the ∼5 km 2 TAG Hydrothermal Field (Rona et al, 1993;Lehrmann et al, 2018), but are geographically isolated from the active mounds (at least at the surface). Other large sulfide accumulations may be found on intermediate spreading ridges as well as in island arc environments and marginal basins (Hannington and Monecke, 2009;Cherkashov, 2017).…”
Section: Initial Discoveriesmentioning
confidence: 99%
“…(b) Conductivity models across TAG mound. (c) Porosity versus conductivity of selected samples from TAG (stars) and other sources (rectangles) for basalt (black), sulfide (red), and jasper (blue, a thin, <1‐m, silicate‐based layer above the sulfides; Lehrmann et al, ) samples; the Hashin Shtrikman upper bound (solid line) separates the main conduction mode via electrolytes (left) and metals/semiconductors (right), and the dashed line represents Archie's law approximation for electrolytic conduction in hard rock (Evans & Everett, ; Müller et al, ) with a =1 and m =1.8. TAG = Trans‐Atlantic Geotraverse.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies with a seafloor EM transmitter and receiver spacings of <100 m (Cairns et al, ) revealed higher conductivities (up to ∼16 S/m), similar to the conductivities for a similar penetration depth of the MARTEMIS system at the inactive deposits (Haroon et al, ) which suggests that the generally lower conductivities observed with the DASI‐Vulcan system at TAG mound are probably related to the deeper penetration depth due to the larger transmitter‐receiver spacing (350 and 505 m) and resulting averaging between highly conductive material just beneath the seafloor and less conductive stockwork material at greater depth. The smaller size of the TAG mound compared to the inactive deposits may in this case play a larger role than the possible effects of anhydrite (Lehrmann et al, ; Murton et al, ) and hot fluids (∼360 °C) which are only present in the active system.…”
Section: Discussionmentioning
confidence: 97%
“…This assumption is supported by the dominant and minor abundance of chalcopyrite and secondary Cu-mineral assemblages (Table 2), and higher Cu (5.19 wt.%) contents in bulk sediment (Table 3) at TVG-10. A previous study [34] has suggested Fe-dominated mineral assemblages in extinct sulfide mounds in the TAG hydrothermal field. Also, the calculated sphalerite precipitation temperature (~233 • C, n = 5) further suggests the occurrence of a low-intermediate temperature hydrothermal venting, rather than extinction at TVG-10.…”
Section: The Contributions Of Hydrothermal Fluid Evidence From S Isomentioning
confidence: 86%
“…The results of 10 representative bulk sulfur isotope analysis (δ 34 S) are shown in Table 6. The δ 34 S values of the Wocan-1 sediment varied spatially from 3.0-3.6‰, from station TVG-08 to TVG-07 (mean value; 3.45‰, n = 4). The Wocan-2 sediments were slightly broader and heavier and varied spatially from 4.1-4.3‰ and 6.4-8.7‰ at station TVG-10 to TVG-05 ( Figure 3), mean value; 6.28‰, n = 6).…”
Section: Sulfur Isotopesmentioning
confidence: 99%